Upaya Peningkatan Efisiensi Transformator Dengan Manajemen Trafo di.Pt PLN (Persero) ULP Benjeng - Muhammad Anshori; Hadi Tasmono (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Electrical power is a very important source for life. One of the electrical components is a distribution transformer which is used to transmit electrical voltage from the substation to the load center. Every year the electricity demand increases, so that the transformer works optimally, you must also pay attention to the loading. Load imbalance on electric power distribution transformers always occurs and this imbalance occurs due to the use of electrical energy. The current flowing in the neutral conductor of the transformer causes an imbalance in the transformer load and losses, namely losses due to the neutral current in the neutral conductor of the transformer. When analyzing mass, use quantitative methods. After analysis, it shows that the transformer is in an unbalanced state where neutral current appears in the transformer. To determine the efficiency of the distribution transformer